Halal Fashion Value Chain and Local Economic Empowerment: The Case of Pekalongan City, Indonesia - Indah Purwanti; Annisa Rizkikaddhuhani (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
The industrial sector has increasingly become a catalyst for economic transformation inIndonesia, particularly as agricultural land conversion and labor shifts accelerate urbanindustrialization. Within this process, the halal industry has emerged as a strategic field due tothe growing global demand for halal-certified products. Pekalongan City, historically recognizedfor its textile and batik production, represents one of Indonesia’sleading creative hubs in halalfashion. This study aims to analyze the structure of the halal fashion value chain and its socioeconomic implications for local communities in Pekalongan. Employing a qualitative approachthrough literature review and field interviews, the research examines the positioning ofPekalongan within the global halal fashion ecosystem. The findings reveal that Indonesiaremains a net importer in the global halal fashion trade, with the industry’s economic valuelagging behind the halal food and beverage sector. In Pekalongan, halal fashion activities areconcentrated on domestic markets, while export participation and certification adoption remainlimited. The study concludes that the halal fashion ecosystem in Pekalongan is still in itsformative stage and requires integrated support in value chain development, export facilitation,and institutional coordination to enhance global competitiveness.